Da prevenção à incriminação: os múltiplos sentidos da abordagem policial - Risso, Melina Ingrid (2018)
This study aims to contribute to the analysis of police stop-and-frisk in the Brazilian context, seeking to identify the meanings attributed to this practice in the state of São Paulo. Using an interpretive approach, the work aims to identify and compare the meanings of the stop-and-frisk policy both in terms of its formulation and implementation. It also seeks to infer to what extent the relationship between the police and the community interferes with the way police officers implement stop-and-frisk policy. The research discusses how the current stop-and-frisk policy affects police officers’ authority and police legitimacy. Annually, the Military Police of the state of São Paulo conducts more than 14 million stop-and-frisks without critical evaluation of their effectiveness. Qualitative methods based on interviews and document analysis were used.